The Effect of Modulated Millimeter Electromagnetic Waves of Non-Thermal Intensity on the Physical Properties of Aqueous Solutions - Kalantaryan, V. P.; Sogomonyan, L. R.; Ghazaryan, R. S.; Babayan, Yu. S.
The surface tension and density of bi-distilled water, water salt solution and salt solutions of the DNA, irradiated by non-thermal millimeter electromagnetic waves with the frequencies 64.5 GHz, 50.3 GHz and 48.3 GHz with modulation 1 Hz and 16 Hz are investigated. The measurements of test samples show that due to irradiation the surface tension does not change. The densities of water salt solution and the salt solutions of the DNA increase under irradiation at the frequencies 64.5 GHz and 50.3 GHz with modulation 1 Hz. When modulated with a frequency of 16 Hz, the density increases at a carrier frequency of 64.5 GHz and decreases at a carrier frequency of 50.3 GHz which coincides with the resonant frequencies of oscillations of water hexagonal structures.
Keywords: Physics